Pengaruh Sales Growth, Karakter Eksekutif, Dan Capital Intensity Terhadap Tax Avoidance: Studi Empiris Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2021 - Alika Ayustina; Mohamad Safi'i (Politeknik Negeri Padang, 2023)
This study aims to determine the effect of sales growth, executive character and capital intensity on tax avoidance. Tax avoidance is the dependent variable and sales growth, executive character and capital intensity are independent variables. This type of research is quantitative, with a population of 60. This research was conducted on manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2021, the research sample was 10 companies with 6 years of observation, the method of determining the sample used was purposive sampling. The analysis method uses panel data regression analysis, T test and F test using Eviews 12. The results show that sales growth and executive character have no effect on tax avoidance and capital intensity has no effect on tax avoidance. Meanwhile, sales growth, executive character and capital intensity have a simultaneous effect on tax avoidance with a significance of 0,000377 < 0,05.